Characterisation of Arabidopsis thaliana heat-responsive RNA-binding protein (HRR) gene: molecular roles in plant thermotolerance and development - Oliveira, Juliana Cabral (2012)
Tese de doutoramento em Ciências (área de especialização em Biologia)